The Impact of YouTube Tutorials on Skills Acquisition: As an Effective Educational Tools: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The implementation of limited face-to-face classes is limiting students' learning pace.YouTube has the potential to fill the gap in the classroom as an educational tool. YouTubevideos integrate verbal and visual components. They provide comprehensive content; as aresult, many academic skills are acquired. However, there's a common issue of obstacles inaccessing YouTube during online learning. They are unable to benefit from the educationalvideos on YouTube. Furthermore, the learners wanted to educate themselves voluntarily, andthe references in the videos they watch on YouTube are generally for entertainment, whichmay cause a distraction for the learners. YouTube is a useful tool that can improve thelearning experience if the video is, in fact, pertinent to the topic at hand. This study aims toknow the impact of YouTube on skills acquisition on the learners and ensure the effectivenessof YouTube as an educational tool that they may use to broaden the learning environment.The study revealed that there is a problem in accessing YouTube on skills acquisition.However, despite the problems they encountered, there is still a positive impact, and learnerscan be responsible, committed to surviving, and flexible in this kind of learning. Researchersconcluded that regardless of the problem of the learners caused by the problems encounteredin Youtube, learners are still responsible in this kind of learning environment.YouTube has had a significant impact on classroom management advantages for bothstudents and teachers. From the students' perspectives on the usage of YouTube for learning,there are corresponding usage patterns and related factors prompting them to use YouTube.The YouTube benefits include attracting students' attention, maintaining their focus, watchingchallenging occurrences, piquing their interest in the subject matter, improving contentattitudes, improving content attitudes, building relationships with students, encouraginginnovation, fostering teamwork, and motivating students. The researchers recommendencouraging and advising teachers to use YouTube in their own courses to take advantage ofits built-in advantages in the context of learning and teaching. In accordance with the (LMS)the newest eLearning-resources that can be included in modern education teaching isYouTube.
Keywords: Education